Smile 2.0 / Rozana Othman … [et al.] - Othman, Rozana; Alias, Nurul Ezaili; Ramly, Fariha Aiza; Mastor, Suraya Hamimi; Ismail, Shafinar (Division of Research and Industry Linkages, 2017)
The transition of traditional learning management systems (LMS) to social media and technology has becoming a vital element of education for learners of all ages (Greenhow, C„ & Lewin, C„ 2016). Social media and technology is transforming the ways how people communicate, collaborate, learn and this phenomenon are not omitted in higher education (Gleason, B„ 2016). Subsequently, an informal learning technique by using Facebook has been increasingly used to enhance communication, collaborate, and learning among students on any current issues that related to their courses (Manca, S„ & Ranieri, M, 2016), Most importantly, a particular group is created as a forum for discussions. The lecturer will then initiate topics and, for each topic, conversations and debates ensue (Manasijevic, D„ Ziivkovic, D„ Arsic, S., & Milosevic, I., 2016). In this case, the lecturer has initiated a Facebook group to discuss on topic of Industrial Relations Current Issues either globally or locally. The objectives of this technique are (i) to encourage the students to have interactive learning by letting out their views on respective current issues that have been initiated by the lecturers, (ii) to ease the [earning process for students remotely, (iii) this Facebook group can help gather all the current issues being discussed by the students, hence, students can save more time by only referring to one page only. In fact, this technique has been practiced in the classroom, however, it is NOT YET enshrined in the syllabus as one of the learning activities by the students for subject code HRM659 (Industrial Relations) And HRM542 (Recruitement and Selection), The special criteria of this technique is offering a platform for students to write articles on any Industrial Relations issues and able to share their ideas and opinions to everyone through Facebook. Therefore, this innovation will introduce a new learning activity, called as Social Media Informal Learning (SMILe), in order to ensure the students are been equipped with all current issues and knowledge for Industrial Relations course,